Initial 3‐year outcomes with left ventricular assist devices in a country with a nascent heart transplantation program. (30th October 2015) - Pya, Yuriy; Bekbossynova, Makhabbat; Jetybayeva, Saltanat; Bekbossynov, Serik; Andossova, Saltanat; Salov, Roman; Medressova, Assel; Novikova, Svetlana; Murzagaliyev, Muradym
Abstract: Aims: The need for the left ventricular assist devices (LVAD) in patients with end‐stage heart failure is well established, but prior to 2011, this was not available to patients in Kazakhstan. We describe the development of the sole LVAD programme in the context of a nascent heart transplantation programme and clinical outcomes for the first three years. Methods and results: From November 2011 to November 2014, 146 patients underwent implantation of 152 VADs (approximately 50 devices implanted per year). We retrospectively analyzed data from 135 LVAD patients who received HeartMate II ( n  = 95) or HeartWare ( n  = 40) devices. In 75 patients LVAD was used as a bridge‐to‐transplantation and in 60 patients as destination therapy, but only 3 of 135 LVAD patients received heart transplant. Forty‐three patients of the LVAD cohort had died by the end of the follow‐up period. The mean time on LVAD was 466 ± 330 days (range 5–1200 days). Kaplan–Meier survival estimates for patients who continued on LVAD support were 93% after 1 month, 86% after 6 months and 77% after 12 months. The most common complications within the first 30 days after implant included right ventricular failure ( n  = 20, 1.85 events/patient‐year), renal failure ( n  = 19, 1.76 events/patient‐year) and bleeding ( n  = 33, 3.0 events/patient‐year). Beyond 30 days adverse events included driveline infections ( n  = 46, 0.56 events/patient‐year) and stroke ( n  = 33, 0.21 events/patient‐year). Conclusions: LVADs are an important therapeutic alternative to heart transplantation in the context of a developing heart transplant programme with outcomes that are comparable to those reported by other centres.